Identification and frequency of circulating CD4+ T lymphocytes specific to Benzylpenicillin in healthy donors. Issue 7 (10th June 2013) - Nhim, C.; Delluc, S.; Halgand, F.; de, L.; Weaver, R. J.; Claude, N.; Joseph, D.; Maillère, B.; Pallardy, M.
Abstract Background Drug hypersensitivity is known to rely on a drug‐specific T‐cell response. Amplitude of antigen‐specific T‐cell response is partly controlled by the size of the antigen‐specific naïve CD4+ T‐cell repertoire, but estimate of this repertoire has never been investigated for allergenic drugs. The purpose of this study was to evaluate the frequency of benzylpenicillin‐specific CD4+ T lymphocytes in healthy donors. Methods Co‐cultures were established with CD4+ T lymphocytes from healthy donors and mature autologous dendritic cells loaded with benzylpenicillin coupled to human serum albumin. CD4+ T lymphocytes were stimulated once a week for 4 weeks with benzylpenicillin coupled to human serum albumin. The CD4+ T‐cell response was measured using an interferon‐γ ELISPOT assay. Frequency of benzylpenicillin‐specific naive CD4+ T lymphocytes was then calculated using the Poisson distribution law. Results Results showed the presence of benzylpenicillin‐specific CD4+ T lymphocytes in 9 of 10 tested healthy donors irrespective of their HLA typing, with a mean frequency of 0.29 cells per million of CD4+ T cells. Experiments performed on naive (CD45RA+) and on memory (CD45RO+) CD4+ T lymphocytes showed that these benzylpenicillin‐specific CD4+ T lymphocytes belonged to the naive T‐cell subpopulation. Conclusion This study showed for the first time the existence of naive CD4+ T lymphocytes specific to benzylpenicillin in healthy donors.